Methacycline displays a strong efficacy in reducing toxicity in a SCA3 Caenorhabditis elegans model - Amigoni, Loredana; Airoldi, Cristina; Natalello, Antonino; Romeo, Margherita; Diomede, Luisa; Tortora, Paolo; Regonesi, Maria Elena (Biochimica et biophysica acta. General subjects, 2019)
We have previously demonstrated the neuroprotective activity of tetracycline on a Spinocerebellar Ataxia 3 nematode model. Here, we present the screening of a small library of tetracycline congeners in order to identify the most effective compound in preventing ataxin-3 aggregation. We performed the assays on the Josephin Domain as it is directly involved in the onset of fibrillation. We used thioflavin T and solubility assays to spot out the most effective tetracycline congeners; Fourier transform infrared and NMR spectroscopies to characterize their mode of action. We employed an ataxic Caenorhabditis elegans model to evaluate the pharmacological efficacy of tetracycline congeners. Methacycline was identified as the most effective compound. Like tetracycline, methacycline neither significantly affected the aggregation kinetics nor did it change the secondary structures of the final aggregates but increased the solubility of the aggregated species. Saturation transfer NMR experiments demonstrated methacycline capability to only bind the oligomeric species of Josephin Domain. Competition assays also showed that methacycline binds to the Josephin Domain more tightly than tetracycline. The treatment with methacycline induced a significant improvement in motility and locomotion of the transgenic C. elegans without changing its lifespan. The efficacy was distinctly stronger than that of tetracycline. Noteworthy, unlike tetracycline, methacycline was able to retard aging-related decline in motility of even the healthy worms used. The apparent absence of toxic effects displayed by methacycline, along with its stronger efficacy in contrasting expanded ataxin-3 toxicity, makes it a possible candidate for a chronic treatment of the disease. •Methacycline effectively retards time-dependent precipitation of Josephin domain (JD).•Its effects on JD structure are similar to those of tetracycline, as shown in FTIR.•However, methacycline interacts more tightly with JD, as shown in STD NMR.•It is also much more effective in preventing motility decline in ataxic nematodes.•Remarkably, it also reduces the age-related motility decline in healthy worms.